A powered prosthetic ankle joint for walking and running. Issue 3 (December 2016) - Grimmer, Martin; Holgate, Matthew; Holgate, Robert; Boehler, Alexander; Ward, Jeffrey; Hollander, Kevin; Sugar, Thomas; Seyfarth, André
Abstract Background Current prosthetic ankle joints are designed either for walking or for running. In order to mimic the capabilities of an able-bodied, a powered prosthetic ankle for walking and running was designed. A powered system has the potential to reduce the limitations in range of motion and positive work output of passive walking and running feet. Methods To perform the experiments a controller capable of transitions between standing, walking, and running with speed adaptations was developed. In the first case study the system was mounted on an ankle bypass in parallel with the foot of a non-amputee subject. By this method the functionality of hardware and controller was proven. Results The Walk-Run ankle was capable of mimicking desired torque and angle trajectories in walking and running up to 2.6 m/s. At 4 m/s running, ankle angle could be matched while ankle torque could not. Limited ankle output power resulting from a suboptimal spring stiffness value was identified as a main reason. Conclusions Further studies have to show to what extent the findings can be transferred to amputees.